Preimplantation embryotoxicity after mouse embryo exposition to reactive oxygen species - Cebral, E. (2007)
Exposure of either gametes or embryos to conditions and/or factors that generate oxidative stress has been associated with impaired early embryogenesis. The effects of reactive oxygen species (ROS) on mouse preimplantation development, depending of the ROS-concentration and time of exposition, were studied. Two-cell embryos were incubated with 5, 10, 25 and 50 μM of hydrogen peroxide (H2O2) for 30 and 60 minutes of exposition and allowed to develop for 72 h to study the quality of development. The incubation with 50 μM H2O2 for 30 or 60 minutes, strongly inhibited the 2-cell embryo development as compared to the control (p<0.001). Twenty-five μM H2O2 produced inhibition of blastocyst formation (p<0.001) and 10 μM H2O2 significantly decreased the percentages of expanded and hatched blastocysts, which resulted morphologically altered (p<0.05 and p<0.01, respectively). The higher H2O2 concentrations were able to elicit necrotic morphology in the 2-cell arrested embryos, while 10 μM H2O 2 induced moderate damage with the arrested embryos partially fragmented. In conclusion, important causes for defective preimplantation development and for early embryo losses may be due to oxidative stress because early mouse embryos exposed to ROS for short times arrested at the first cellular cycle (2-cell) and/or impaired embryo differentiation and morphogenesis, being these effects ROS-concentration-dependent.